News and Views on Polysialic Acid: From Tumor Progression and Brain Development to Psychiatric Disorders, Neurodegeneration, Myelin Repair and Immunomodulation - Thiesler, Hauke; Küçükerden, Melike; Gretenkort, Lina; Röckle, Iris; Hildebrandt, Herbert (Frontiers in Cell and Developmental Biology, 2022)
Polysialic acid (polySia) is a sugar homopolymer consisting of at least eight glycosidically linked sialic acid units. It is a posttranslational modification of a limited number of proteins with the neural cell adhesion molecule NCAM being the most prominent. As extensively reviewed before, polySia-NCAM is crucial for brain development and synaptic plasticity but also modulates tumor growth and malignancy. Functions of polySia have been attributed to its polyanionic character, its spatial expansion into the extracellular space and its modulation of NCAM interactions. In this mini-review, we first summarize briefly, how the modulation of NCAM functions by polySia impacts tumor cell growth and leads to malformations during brain development of polySia-deficient mice, with a focus on how the latter may be linked to altered behaviors in the mouse model and to neurodevelopmental predispositions to psychiatric disorders. We then elaborate on the implications of polySia functions in hippocampal plasticity, learning and memory of mice in light of recently described polySia changes related to altered neurogenesis in the aging human brain and in neurodegenerative disease. Furthermore, we highlight recent progress that extends the range of polySia functions across diverse fields of neurobiology such as cortical interneuron development and connectivity, myelination and myelin repair, or the regulation of microglia activity. We discuss possible common and distinct mechanisms that may underlie these seemingly divergent roles of polySia, and provide prospects for new therapeutic approaches building on our improved understanding of polySia functions.